IMPACT OF SELECTED MACROECONOMIC FACTORS FOR BALANCE OF FOREIGN TRADE (Research Bulletins of the Faculty of Economic Sciences, 2021)
This paper presents the results of studies on the effects of selected macroeconomic variables: USD exchange rate, interest rate, Gross Domestic Product, inflation rate and unemployment rate for exports and imports of goods and the trade balance in Poland. The study used the classical method (Pearson correlation coefficient) and non-classical method (Granger causality test).
Keywords: imports, exports, trade balance, macroeconomic factors.